2019
DOI: 10.1016/j.brainres.2018.12.038
|View full text |Cite
|
Sign up to set email alerts
|

PrP-grafted antibodies bind certain amyloid β-protein aggregates, but do not prevent toxicity

Abstract: Background The prion protein (PrP) is known to bind certain soluble aggregates of the amyloid β-protein (Aβ), and two regions of PrP, one centered around residues 19-33, and the other around 87-112, are thought to be particularly important for this interaction. When either of these sequences are grafted into a human IgG the resulting antibodies react with disease-associated PrP conformers, whereas the parental b12 IgG does not.Methods Human antibodies containing grafts of PrP 19-33 or 87-112 were prepared as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 54 publications
(66 reference statements)
0
20
0
Order By: Relevance
“…It will fall to future studies to purify soluble protein aggregates from diseased brain and to test their toxic activities. In this regard, our recent observation that recombinant PrP N1 can protect against the toxicity of brain-derived Aβ [62] suggests that PrP derivatives such as N1 may serve as affinity reagents to enable the isolation and molecular identification of SPAs. Similarly, in vivo studies will be required to further investigate the translational nature of our work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It will fall to future studies to purify soluble protein aggregates from diseased brain and to test their toxic activities. In this regard, our recent observation that recombinant PrP N1 can protect against the toxicity of brain-derived Aβ [62] suggests that PrP derivatives such as N1 may serve as affinity reagents to enable the isolation and molecular identification of SPAs. Similarly, in vivo studies will be required to further investigate the translational nature of our work.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, SPAs of tau and αSyn bound to PrP with high affinity, but (as with Aβ) monomers and end-stage fibrils displayed little or no binding. Moreover, anti-PrP antibodies to the putative Aβ binding Sites I and II [19,31,32,62] effectively displaced SPAs of αSyn and tau, and deletion of these sites substantially attenuated binding. Multielectrode recordings from hippocampal slices of PrP WT mice revealed that soluble aggregates (but not monomers) of Aβ, tau and αSyn impair LTP, and recordings from PrP null mice demonstrate that this impairment required expression of PrP.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our experiments, cytoplasmic N1 did neither confer protection against prions nor against Aβinduced neurotoxicity. Since exogenously administered N1 reliably blocks Aβ-induced neurotoxicity [38,[64][65][66][67][68][69][70][71], our data rather support a model where Aβinduced neurotoxicity is mainly executed by events occurring at the plasma membrane of neurons. Fig.…”
Section: No Protection Of Cytosolic N1 Against Proteopathic Seedsmentioning
confidence: 41%
“…As a soluble ligand, N1 acts beneficial in several ways as it reduces hypoxia-induced neuronal damage [61] and may be involved in myelin maintenance [62] and intercellular communication (reviewed in [63]). With regard to AD, numerous studies have shown that exogenously administered N1 and N1-like peptides are able to block toxic Aβ oligomers and interfere with their synaptic impairment and neurotoxicity [38,[64][65][66][67][68][69][70][71].…”
Section: Introductionmentioning
confidence: 99%